Analysis of twitter user sentiment on the monkeypox virus issue using the nrc lexicon - Muhammad Khahfi Zuhanda; Anil Hakim Syofra Syofra; Devy Mathelinea; Prana Ugiana Gio; Yuan Anisa Anisa; Nanda Novita (Institute of Computer Science (IOCS), 2023)
Monkeypox virus is closely related to variola (smallpox virus) and causes a smallpox-like disease. The increase in monkeypox cases has caused the general public to be involved in providing responses to seek and share information related to monkeypox on the internet, especially on social media platforms. This study aims to analyze a collection of 5000 tweets on August 5, 2022, for sentiment analysis using the NRC lexicon. Of the 5,000 tweets that have been extracted, it is obtained that the words that Twitter users often use are